OP0040 MODIFIED IMMUNE CELL THERAPY AMELIORATES MURINE LUPUS NEPHRITIS AND INDUCES REGULATORY CELL SUBSETS. (June 2019) - Speer, Claudius; Kim, Daniela; Kleist, Christian; Schmitt, Anita; Schmitt, Michael; Sommerer, Claudia; Steinborn, Andrea; Kälble, Florian; Nusshag, Christian; Wang, Lei; Kunz, Alexander; Lorenz, Hanns-Martin; et al.
Abstract : Background: Modified immune cells (MICs) are mononuclear cells that gain immunosuppressive properties after incubation with the proliferation inhibitor mitomycin C. We recently showed that syngeneic MIC therapy controlled experimental autoimmune encephalitis (EAE) (1). In addition, allogeneic MIC therapy prevented rejection in rat heart and hindlimb as well as pig kidney transplantation (2). Objectives: We now wanted to translate these encouraging findings to the prevention and treatment of lupus nephritis. Methods: Splenocytes of syngeneic NZB/W F1 (BWF1) donor mice were incubated with mitomycin C and injected into recipient's tail vein after matching for age and disease activity. Group 1 received no MIC therapy, group 2 standard-dose MIC therapy with 1.5x10 8 /kg BW once and group 3 repeated MIC therapy with 1.5x10 8 /kg BW at weeks 1, 2 and 3. Group 4 received MIC infusions before disease onset as preemptive treatment approach. Disease activity was monitored by loss of body weight, protein excretion, serum creatinine and dsDNA antibodies. Combined primary endpoint was day 40 post-treatment, protein excretion ≥3g/l for 2 consecutive weeks and >30% loss of original body weight. Histopathology with PAS and HE staining was performed to assess degree of lupus nephritis. Regulatory cell subsets were measured in peripheral blood. Results: MIC therapy prevented the progression of fatal lupus nephritis in BWF1 mice. Protein excretion, serum creatinine and dsDNA antibodies were lower in standard-dose (group 2) and preemptive (group 4) groups compared to control group (group 1) whereas repeated MIC therapy after disease onset had no effect (Figure 1A-E). The primary endpoint was reached significantly more often in control group (group 1, 67%) compared to treatment groups 2 (14%), 3 (14%) and 4 (0%) (Figure 1F). Renal architecture was preserved in different MIC treatment groups (groups 2-4) with decreased glomerular and tubular damage scores (Figure 1G). Most importantly, frequencies of CD8 + CD25 + FoxP3 + regulatory T cells and CD19 + CD5 + CD1d high regulatory B cells were significantly higher in MIC-treated (groups 2-4) compared to control animals of group 1, whereas double negative T cells were markedly reduced (Figure 1H). Conclusion: MIC therapy inhibits progression of active lupus nephritis. Interestingly, preemptive MIC therapy was even able to prevent onset of disease with no significant disease activity at completion of the study. In accordance with our previous pre-clinical EAE experiments (1) and a first in-human clinical trial in living-donor kidney transplantation (TOL-1 study), MIC therapy was able to induce an in-vivo induction of regulatory cell subsets. This clinically applicable cell therapeutic approach may control lupus nephritis by specifically silencing deleterious autoimmune responses. References: [1] Terness P, Oelert T, et al. Mitomycin C-treated dendritic cells inactivate autoreactive T cells: toward the development of a tolerogenic vaccine in autoimmune diseases. Proc Natl Acad Sci USA. 2008 Nov 25;105(47):18442–7. [2] Jiga LP, Ehser S, Kleist C, Opelz G, Terness P. Inhibition of heart allograft rejection with mitomycin C-treated donor dendritic cells. Transplantation. 2007 Feb 15;83(3):347–50. Disclosure of Interests: Claudius Speer Grant/research support from: Research Grant from TolerogenixX GmbH, Daniela Kim Grant/research support from: Research Grant from TolerogenixX GmbH, Christian Kleist Shareholder of: TolerogenixX GmbH, Anita Schmitt Shareholder of: TolerogenixX GmbH, Michael Schmitt: None declared, Claudia Sommerer: None declared, Andrea Steinborn: None declared, Florian Kälble: None declared, Christian Nusshag: None declared, Lei Wang Grant/research support from: Research Grant from TolerogenixX GmbH, Employee of: TolerogenixX GmbH, Alexander Kunz Grant/research support from: Research Grant from TolerogenixX GmbH, Employee of: TolerogenixX GmbH, Hanns-Martin Lorenz: None declared, Martin Zeier: None declared, Christian Morath Shareholder of: TolerogenixX GmbH, Matthias Schaier Shareholder of: TolerogenixX GmbH